Technological mediation and social isolation in Dave Eggers’s The Circle (2013): A Foucauldian perspective - Alshamsi , Aysha Juma; Alqaryouti, Marwan; Alali, Omar; Al-Abbas, Linda S (Research Journal in Advanced Humanities, 2026)
In this essay, I will discuss the relationship between technological mediation and the isolation of humans in the writings of Dave Eggers, paying special attention to The Circle (2013). In his discussion, the author suggests that Dave Eggers addresses the issue of digital culture and the influence that such factors as surveillance, data transparency, and algorithms have on characters' lives. Based on the theories of digital humanities and panopticism, which Michel Foucault described in his book, Discipline and Punish: The Birth of the Prison (1975), this paper explains the role of technology in forming the modern panopticon and producing self-monitored individuals. With the use of textual analysis, this essay demonstrates that the novel not only describes technology as the tool for connecting people but rather the factor that increases their emotional separation, undermines the value of their privacy, and changes them from ordinary humans into performative beings who are motivated by numerical measures of success like likes, rating, and visibility. Also, the paper argues that through his novel, Eggers opposes the notion of connectivity and illustrates how, by fulfilling that ideology, one ends up being more isolated despite constant communication. As such, the paper contributes to the discussion surrounding The Circle by placing it within the context of surveillance capitalism and the construction of the digital self in the contemporary literary conversation.